Organization as a subject - Ćwiklicki, Marek (Journal of Public Governance, 2014)
The purpose of this paper is to present the results of analyses of the methodological approaches which consider organization as an entity. The author discusses the limitations of such a procedure, but also presents arguments that confirm the thesis formulated in the title. In the conclusion of the paper, the author offers a critical discussion and a list of statements justifying the treatment of an organization as a subject.